The New Turkish Republic: By Graham E. Fuller (Washington, DC: United States Institute of Peace Press, 2008. 196 pages.) (American Journal of Islam and Society, 2008)
This policy book purports to advise American decision makers about thechanges and transformations taking place in Turkey’s politics and foreignpolicy, as well as their reasons and implications. It further counselsWashington on how to deal with the novelties that they may engender. Graham Fullerargues that Turkey, under Mustafa Kemal Ataturk and his successors, underwentan imposed “cultural lobotomy” designed to induce a national “amnesia”about its Islamic and Ottoman past (p. 17). This condition, however, isending, for Turkey seems to be experiencing a counter-dynamic and a “returnof history,” away from what the author deems a “transient geopolitical aberrationfrom a long norm” (p. 8).Fuller makes his point by asserting, first, that Turkey is again becomingpart of the Middle East and examining its historical trajectory and legacies.Second, by highlighting the increasing divergence in Turkish-Americanrelations due to the changing circumstances related to the Soviet collapseand the reordering of European politics, he sees an American regionalagenda at odds with Turkish national and geopolitical interests, as well as aTurkish strategic opening to the Muslim world, Eurasia, Russia, and China,as alternative political and economic options. The author’s broad conclusionis that how Turkey will act in the Middle East and the Muslim world willlargely depend on the “complex interplay” between the United States, theEuropean Union, and Turkey’s non-western interests (p. 9). Such a “comeback,”in any case, is likely to partially dilute and complicate, as well asenrich and complement, Turkey’s links with the “West” (p. 8) ...